Pembuatan Video YouTube Channel untuk Pembelajaran Bahasa Inggris di Madrasah Aliyah Kelas X - Awaluddin Syamsu; Hadijah Hadijah (Universitas Pahlawan Tuanku Tambusai, 2022)
The Covid-19 pandemic has impacted Indonesian’s educational system. The learning system must be conducted online. Students who used to study in class currently have to study at home. After the pandemic cases declined, students have started to return to school but with various restrictions. One of the solutions of the situation is to combine online and offline which is a new thing in Indonesia’s education for senior high school students. YouTube Channel is one of the blended learning solutions where students can watch their learning videos at home and in class. The created videos were in accordance with the context of the X grade of Madrasah Aliyah students who are the objects of our social service program. This social service used the mentoring method to 17 students and 2 English teachers. The results show that there are many things that must be considered in making a video but the most import are short duration, interesting display and in accordance with the school curriculum. The results of this social service will be used by the school and become a reference in developing learning videos on the YouTube Channel